Radio Drama in ESL Learning among Engineering and Business Students in UiTM Kampus Pasir Gudang - Sa’adan, Nadzrah; Taib, Siti Aishah; Saidalvi, Aminabibi; Ismail, Mohd Erfy (Human Resource Management Academic Research Society, 2022)
A radio play is a dramaticized acoustic performance. Radio drama feature lacks a visual component, mainly depends on speech, music, and sound effects to let the listener imagine the characters and story. There are many studies done on the effectiveness of role-playing, theater, and drama but not many studies done on radio drama. The purpose of this study is to investigate the students’ opinions on the effects of radio drama on their language skills. As many as 96 respondents who have been involved in this study are requested to answer a questionnaire regarding the effects of radio drama on their language skills. The study employed quantitative method analysis. Statistical analysis was also conducted to find out the significant difference between two main variables in the study namely business students and engineering students. The findings of the study show that majority of the students from both groups believed that radio drama application in ESL learning brings good effects to their language skills; writing, speaking, reading, and listening. The students believed that it has helped them to enhance their creativity, range of vocabulary, pronunciation, and grammar skills.